Cropping potential or the red-laterite-gravelly belt of West Bengal based on moisture availability index and soil characteristics - SARKAR, JAYANTA; BISWAS, B. C. (MAUSAM, 1996)
Crop potential has been brought out over the red-laterite-gravelly belt of West Bengal using Moisture Availability Index (MAI) and broad soil information. MAI indicates that a crop of 15. 18-20 and 22-24 weeks. duration at 80%, 50% and 30% probability levels respectively maybe raised from this belt. In most of the stations of the belt, rice could be raised in eight out of every ten years without encountering much waterstress period. At lower probability levels. after rice, pulses like gram. tur and lentil and oilseeds like rapeseed and mustard may be raised based on residual soil moisture. In low rainfall years sorghum. groundnut, maize could be introduced in place of rice in the kharif season. Emphasis should also be given on agro-forestry and horticultural crops for increasing and stabilizing agricultural production.